HaRePo (harm reduction by post): an innovative and effective harm reduction programme for people who use drugs using email, telephone, and post service - Magally Torres-Leguizamon; Emmanuel G. Reynaud; Thomas Néfau; Catherine Duplessy (BMC, 2020)
Abstract Background Despite multiple harm reduction (HR) programmes worldwide, there are still an important number of people who use drugs (PWUD) who do not access those services. Their difficulties to obtain HR tools are due to their inability to reach such services (remoteness and/or limited customer service hours), costs, quantitative restrictions, fear of judgement, lack of confidentiality in pharmacy, and unfamiliarity with HR programmes. We tested an innovative approach using the power of remote online communication and the national postal distribution network to improve HR tool access and counselling. Methods Based on these observations, SAFE association created HaRePo in 2011, a free and confidential programme designed for people who have difficulties accessing HR tools and counselling. PWUD can access the programme by phone and/or email. An HR professional delivers HR counselling and HR tools and connects PWUD to other HR services, medical, and social workers. HR tools are prepared and sent according to the person's needs through the French postal service to consumers across Metropolitan France and overseas territories. Results Since 2011, 1920 PWUD have benefited from HaRePo: 10,450 parcels were sent accounting for more than 1.7 million syringes and 6 million HR-related items. HaRePo receives positive feedback from PWUD who have improved their practices through remote but trusted communication. The percentage of people that, after joining the programme, never reuse and/or share HR tools have significantly increased. On average, 71.5% of beneficiaries never reuse syringes and 81% do not reuse needles. And they are 98.5% consumers who never share syringes and 99% needles any longer. Between 44 and 80% HaRePo beneficiaries have reported that their drug-related practices (injection, inhalation, and snorting) are now safer. Finally, between 39 and 53% HaRePo consumers declared that their overall physical state has improved (e.g. venous condition, the appearance of point of injection, swelling of arms, legs, and hands). Conclusion HaRePo is an innovative HR programme efficient for hard-to-reach PWUD. It shows evidence of a positive feedback loop for PWUD in improving their practices. Finally, HaRePo represents a clear benefit for health authorities in France, who decided to expand the programme in 2016.